Using Portfolio Assessment to Improve Students’ Writing Development - Eka Apriani (Rahis Cendekia Indonesia, 2025)
This study investigates the effectiveness of portfolio assessment in improving students’ writing development in an English as a Foreign Language (EFL) context. Portfolio assessment, which emphasizes continuous progress through drafting, revising, and reflecting, offers an alternative to traditional one-time writing evaluations. The purpose of this research was to examine how the implementation of portfolios influences students’ writing performance and their attitudes toward the writing process. Using a classroom action research design, the study involved cycles of planning, acting, observing, and reflecting. Data were collected through writing tests, observations, student reflections, and teacher field notes. The findings indicate substantial improvement in students’ writing across several components, including content, organization, vocabulary use, grammar accuracy, and mechanics. Students demonstrated greater awareness of the writing process, showed increased motivation, and became more actively engaged in improving their drafts. The reflective activities within the portfolio encouraged deeper metacognitive understanding, enabling students to identify strengths and weaknesses more effectively. Teacher feedback and peer review also played significant roles in supporting students’ revision processes and enhancing the overall quality of their writing. The study concludes that portfolio assessment is a highly beneficial pedagogical approach for writing instruction, fostering autonomy, continuous learning, and more meaningful evaluation. The results suggest that portfolios should be integrated into EFL writing classrooms to support sustained improvement and student-centered learning. Recommendations for further research include examining digital portfolio platforms and investigating the long-term impact of portfolio-based assessment practices.